Hyperglycemic conditions modulate connective tissue reorganization by human vascular smooth muscle cells through stimulation of hyaluronan synthesis. - Sainio A; Jokela T; Tammi MI; Järveläinen H (United Kingdom, 2022)
Changes in the extracellular matrix organization within vascular walls are critical events in the process of atherosclerosis including diabetic macroangiopathy. Here, we examined whether glucose can directly modulate connective tissue reorganization by human vascular smooth muscle cells (VSMCs). Using a collagen gel contraction (CGC) assay, we demonstrated that in comparison with normal glucose concentration (5 mM), high glucose concentration (25 mM) inhibits the efficacy of VSMCs to contract collagen gels. With human genome microarrays, we showed a significant increase in the expression of hyaluronan synthase 2 (HAS2) by VSMCs in hyperglycemic conditions. The finding was verified with quantitative real-time polymerase chain reaction, which also revealed that the expression of the other hyaluronan synthesizing enzymes, HAS1 and HAS3, was stimulated concomitantly. A corresponding increase was observed in hyaluronan (HA) production. Treatment of VSMCs either with hyaluronidase or with 4-methylumbelliferone, an inhibitor of HA synthesis, partially restored the diminished CGC efficacy of VSMCs in hyperglycemic conditions. In conclusion, high glucose concentration stimulated HA synthesis by VSMCs and modulated their ability to reorganize collagen-rich matrix. Because HA is known to enhance the development of atherosclerosis and restenosis after percutaneous coronary interventions, our study provides a new potential mechanism whereby hyperglycemia leads to disturbed vascular remodeling in diabetic patients through stimulation of HA synthesis.